Novel sources of resistance to Septoria nodorum blotch in the Vavilov wheat collection identified by genome-wide association studies - Phan, H.; Rybak, K.; Bertazzoni, S.; Furuki, E.; Dinglasan, E.; Hickey, L.; Oliver, R.; Tan, Kar-Chun (Springer, 2018)
The fungus Parastagonospora nodorum is the causal agent of Septoria nodorum blotch (SNB) of wheat. The pathosystem is mediated by multiple fungal necrotrophic effector–host sensitivity gene interactions that include SnToxA–Tsn1, SnTox1–Snn1, and SnTox3–Snn3. A P. nodorum strain lacking SnToxA, SnTox1, and SnTox3 (toxa13) retained wild-type-like ability to infect some modern wheat cultivars, suggesting evidence of other effector-mediated susceptibility gene interactions or the lack of host resistance genes. To identify genomic regions harbouring such loci, we examined a panel of 295 historic wheat accessions from the N. I. Vavilov Institute of Plant Genetic Resources in Russia, which is comprised of genetically diverse landraces and breeding lines registered from 1920 to 1990. The wheat panel was subjected to effector bioassays, infection with P. nodorum wild type (SN15) and toxa13. In general, SN15 was more virulent than toxa13. Insensitivity to all three effectors contributed significantly to resistance against SN15, but not toxa13. Genome-wide association studies using phenotypes from SN15 infection detected quantitative trait loci (QTL) on chromosomes 1BS (Snn1), 2DS, 5AS, 5BS (Snn3), 3AL, 4AL, 4BS, and 7AS. For toxa13 infection, a QTL was detected on 5AS (similar to SN15), plus two additional QTL on 2DL and 7DL. Analysis of resistance phenotypes indicated that plant breeders may have inadvertently selected for effector insensitivity from 1940 onwards. We identify accessions that can be used to develop bi-parental mapping populations to characterise resistance-associated alleles for subsequent introgression into modern bread wheat to minimise the impact of SNB.